Identification of genomic deletions causing inherited retinal degenerations by coverage analysis of whole exome sequencing data. Issue 9 (22nd April 2016) - Khateb, Samer; Hanany, Mor; Khalaileh, Ayat; Beryozkin, Avigail; Meyer, Segev; Abu-Diab, Alaa; Abu Turky, Fathieh; Mizrahi-Meissonnier, Liliana; Lieberman, Sari; Ben-Yosef, Tamar; Banin, Eyal; Sharon, Dror
Abstract : Background: Inherited retinal degenerations (IRDs) are a common cause of visual disturbance with a high clinical and genetic heterogeneity. Recent sequencing techniques such as whole exome sequencing (WES) contribute to the discovery of novel genes. The aim of the current study was to use WES data to identify large deletions that include at least one exon in known IRD genes. Methods: Patients diagnosed with IRDs underwent a comprehensive ophthalmic evaluation. WES was performed using the NimbleGen V2 paired-end kit and HiSeq 2000. An analysis of exon coverage data was performed on 60 WES samples. Exonic deletions were verified by 'PCR walking' analysis. Results: We analysed data obtained from 60 WES samples of index patients with IRDs. By calculating the average coverage for all exons in the human genome, we were able to identify homozygous and hemizygous deletions of at least one exon in six families (10%), including a single-exon deletion in EYS, deletions of three consecutive exons in MYO7A and NPHP4, deletions of four and eight consecutive exons in RPGR and a multigene deletion on the X-chromosome, including CHM . By using PCR-walking analysis, we were able to identify the borders of five of the deletions and to screen our set of patients for these deletions. Conclusions: We performed here a comprehensive analysis of WES data as a tool for identifying large genomic deletions in patients with IRDs. Our analysis indicates that large deletions are relatively frequent (about 10% of our WES cohort) and should be screened when analysing WES data.